A novel overlap syndrome: Rheumatoid arthritis, Sjogren's syndrome, antiphospholipid syndrome, and dermatomyositis. Issue 4 (24th April 2023) - Mohammed, Maab Jasim; Hashim, Hashim Talib; Al‐Obaidi, Ahmed Dheyaa; Al Shammari, Assim
Abstract : Key Clinical Message: This is an extremely rare case that has not been presented or discussed in the literature to the best of our knowledge. The overlap of connective tissue disease is a challenge for physicians and patients, and it needs special care and regular clinical and laboratory follow‐up. Abstract: This report describes a rare case of overlapping connective tissue diseases in a 42‐year‐old female with rheumatoid arthritis, Sjogren's syndrome, antiphospholipid syndrome, and dermatomyositis. The patient presented with a hyperpigmented erythematous rash, muscle weakness, and pain, highlighting the challenges of diagnosis and treatment that require regular clinical and laboratory follow‐up.